Análisis de las normas técnicas y regulaciones que rigen a las estaciones de radiocomunicación - López, B. (2009)
This document provides a review of technical standards and regulations governing radio stations and provides recommendations applicable in the country. To fulfill the stated objective, the development of this work has been divided into several chapters and a section of recommendations that would provide a better regulation for our regions and more specifically for Ecuador. At first, a rewiew of the definitions and general concepts that are used in radio communication is addressed, that is, the transmission of information through the propagation of radio waves in the atmosphere and space. Later, a study is performed about the different regions in which the earth's surface have been divided in order to make allocations of services in different frequency bands, as well as the atmospheric effects (troposphere and ionosphere) on the radio wave propagation. Specifically, a review is developed on the different allocations of frequency bands for region 2, according to the International Telecommunication Union (ITU) and the Federal Communications Commission (FCC). Finally, a study is achieved on the characteristics, additional regulations and other issues associated with the propagation of radio waves, such as rain attenuation, ionization of the upper and solar radiation, used in providing radio communication services.